Simeprevir and daclatasvir for 12 or 24 weeks in treatment‐naïve patients with hepatitis C virus genotype 1b and advanced liver disease. (13th March 2017) - Hézode, Christophe; Almasio, Piero L.; Bourgeois, Stefan; Buggisch, Peter; Brown, Ashley; Diago, Moises; Horsmans, Yves; Serfaty, Lawrence; Szalay, Ferenc; Gaeta, Giovanni B.; Planas, Ramon; Schlag, Michael; et al.
Abstract: Background & Aims: We investigated the efficacy and safety of simeprevir plus daclatasvir in treatment‐naïve patients with chronic, genotype 1b hepatitis C virus infection and advanced liver disease, excluding patients with pre‐defined NS5A resistance‐associated substitutions. Methods: This phase II, open‐label, single‐arm, multicentre study included patients aged ≥18 years with advanced fibrosis or compensated cirrhosis (METAVIR F3/4). Patients with NS5A‐Y93H or L31M/V resistance‐associated substitutions at screening were excluded. Simeprevir (150 mg)+daclatasvir (60 mg) once daily was administered for 12 or 24 weeks; treatment could be extended to 24 weeks prior to or at the Week 12 visit. Primary efficacy endpoint was sustained virological response 12 weeks after the end of treatment. Results: A total of 106 patients were treated; 27% patients were aged >65 years, 39% had cirrhosis, 53% had estimated glomerular filtration rate 30‐89 mL/min, 14% had diabetes, and 38% had arterial hypertension. Overall, 42/106 received 12 weeks of treatment and 64/106 received 24 weeks of treatment. Ninety‐seven (92%) patients achieved a sustained virological response 12 weeks after the end of treatment. The reasons for failure were viral breakthrough (n=7) at weeks 4‐16, early treatment discontinuation (n=1) and viral relapse (n=1). Seventy‐four (70%) patients had ≥1 adverse event during treatment, including six (6%) patients with ≥1 serious adverse event. Three (3%) patients discontinued treatment owing to adverse events. Conclusions: Simeprevir+daclatasvir demonstrated strong antiviral activity and was well‐tolerated in patients with hepatitis C virus genotype 1b infection, advanced liver disease and a high prevalence of comorbidities. However, viral breakthrough occurred in seven patients, making this regimen unsatisfactory.